Evaluating social funds : a cross-country analysis of community investments - Rawlings, Laura, 1964-; VanDomelen, Julie; Sherburne-Benz, Lynne Darling (Washington, D.C. : World Bank, 2004)
Drawing on a range of methodologies - from randomized control designs to propensity score matching - this study examines the welfare impact of social fund investments in education, health and water and sanitation across six countries.
Includes bibliographical references (p. 197-208).
oif 31/07/15
Loan
Keywords: Community development -- Developing countries -- Evaluation -- Case studies; Economic assistance, Domestic -- Developing countries -- Evaluation -- Case studies